Temperature field detection model based on the dimensional change during the thermal forging process. (25th April 2015) - Zhang, Yu-cun; Fu, Xian-bin; Zhang, Fu-li
Abstract: The temperature of large forgings is a critical technological parameter for improving the forming quality. In order to improve the quality of large forgings, the temperature field detection model is proposed in the paper, and the temperature field is influenced by the dimensional change of forgings. Firstly, combining the measured dimension and the measured temperature, the temperature model in the temperature-drop process is established by the two-dimensional unsteady heat conduction method. Secondly, according to the principle of energy conversion, the plastic work in the process of the dimensional change is converted into heat energy. The conversion coefficient between the plastic work and heat energy is described by a function including the dimensional change and temperature. Using the virtual heat source method in the moving coordinate system, the temperature model in the temperature-rise process is obtained. Finally, the forging temperature detection model is established by the superposition of the two temperature model functions. The feasibility of the model is verified by the experiments and the simulations. This model provides a theoretical basis for improving the quality of forgings. Highlights: Temperature field model is established by the moving heat source method. The internal temperature of forgings is timely calculated by this model. Combining the measured dimension, the heat energy function is further improved. The difference of theoretical temperature and simulated temperature is between 0 and 2%.